Pengaruh Orang Tua yang Acuh Terhadap Religiusitas Anak - Prastika, Cita Ayu; Lolitasya, Anjardita Yosi; Hidayati, Nur Aini (Darul Ilmi: Jurnal Ilmu Kependidikan dan Keislaman, 2023)
Lately, it is often found in the news about young children who commit acts of harassment against their peers. This is a sign that the level of religiosity in children today is relatively low. One of the reasons could be due to the indifference of parents towards children. So that children do not know the action is right or wrong in the eyes of society or religion. Even trivial bad behavior is sometimes still carried out among children and even teenagers to adults. The bad habits that have been done as children will be repeated when they grow up if their parents continue to ignore them. Therefore, the role of parents is needed to provide direction or guidance to children from early childhood to adolescence. The purpose of this study was to find out how indifferent parents influence the child's level of religiosity. Data collection techniques in this study used questionnaires distributed to respondents. The method of data analysis in this study is descriptive analysis to determine the frequency distribution of the findings of data from the field. The answers to the questionnaire are calculated using the percentage formula and then processed and analyzed descriptively to determine whether there is an influence of parents who are indifferent to children's religiosity. The results of this study are that parents are very influential in children's religiosity.